Development of one general and six country-specific algorithms to assess societal health utilities based on ASAS HI - Essers, Ivette; Hiligsmann, Mickael; Kiltz, Uta; Bansback, Nick; Braun, Juergen; van der Heijde, Desirée; Boonen, Annelies (Rheumatic & musculoskeletal diseases open, 2019)
ObjectiveHealth utilities represent preference values that persons attach to health states. This study aims to develop one general and six country-specific algorithms to calculate societal preference values for health of patients with spondyloarthritis (SpA), as assessed by the disease-specific Assessment of SpondyloArthritis international Society Health Index (ASAS HI).MethodsA survey was performed in random population samples from six European countries. In a best-worst choice experiment, subjects were asked to indicate repeatedly which of 4 random aspects of the 17-item ASAS HI was were most and least important. Bayesian analysis provided the relative importance of each of the 17 items. To rescale the relative importance scores on the absolute utility scale between 0 and 1, participants additionally completed two lead time trade-off experiments, one for ‘severe SpA’ and one for ‘best health’ without SpA. Six country-specific algorithms and one general algorithm were derived. The general algorithm was tested in 199 patients with axial SpA (axSpA).Results3039 subjects, mean age 47 years (SD 15) and 52% female completed the experiments. The population’s health utility value for SpA varied between − 0.24 for ‘worst’ SpA (country range −0.35 to 0.03), and 0.88 for ‘best’ health (country range 0.81 to 0.90). Among 199 patients with axSpA, the mean utility was 0.36 (SD 0.30, range −0.24 to 0.88) and discriminated well between patients having high (Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) ≥ 4) or low (BASDAI < 4) disease activity (0.18 (SD 0.24) vs 0.51(SD 0.27), p<0.01).ConclusionOne general and six country-specific algorithms are available to convert scores from the ASAS HI into disease-specific societal utility values.